Towards the low temperature growth of uniform diameter multi walled carbon nanotubes by catalytic chemical vapour deposition technique - Somanathan, Thirunavukkarasu; Pandurangan, Arumugam (Nano-Micro Letters, 2010)
Mesoporous MCM-41 molecular sieves containing f-block transition elements (gadolinium) with various Si/Gd ratios (50, 75 and 100) were synthesised by a hydrothermal method. Their mesoporous structure was confirmed by X-ray diffraction, nitrogen sorption studies, thermogravimetric analysis, scanning and transmission electron microscopy. The local environment of Gd in the material was studied by electron paramagnetic resonance. The compatibility of the catalyst for the synthesis of uniform diameter CNTs by varying the temperature from 400 to 650°C with fixed flow rates of N2 and C2H2 (140 ml/min and 40 ml/min, respectively). The product is mostly metal containing thin MWCNTs with diameter of 10∼20 nm. Characterisation shows that a combination of Gd-MCM-41 (100) catalyst gives a high yield of high quality MWCNTs under optimum growth conditions.